2012
DOI: 10.1021/mp300150q
|View full text |Cite
|
Sign up to set email alerts
|

Forming of Demethoxycurcumin Nanocrystallite-Chitosan Nanocarrier for Controlled Low Dose Cellular Release for Inhibition of the Migration of Vascular Smooth Muscle Cells

Abstract: We report an efficient therapeutic approach to inhibit the migration and growth of vascular smooth muscle cells (VSMCs) via a low-dose sustained elution of a water-insoluble drug, demethoxycurcumin (DMC), through a self-assembled amphiphilic carbomethyl-hexanol chitosan (CHC) nanomatrix. Manipulating the cellular internalization and controlled cytotoxic effect of DMC-CHC nanoparticles over the VSMCs was elucidated. The DMC-CHC nanoparticles, which were systematically characterized in terms of structural morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…These findings are in accordance with previous research demonstrating significant improvement of heart tissue damage in rats treated for myopathy [15]. It is also in line with another study that confirmed that nanocurcumin is an antioxidant and anti-inflammatory with good cardiovascular effects, particularly in reducing migration and growth of uncontrolled vascular smooth muscle cells under hyperglycemic conditions [14].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are in accordance with previous research demonstrating significant improvement of heart tissue damage in rats treated for myopathy [15]. It is also in line with another study that confirmed that nanocurcumin is an antioxidant and anti-inflammatory with good cardiovascular effects, particularly in reducing migration and growth of uncontrolled vascular smooth muscle cells under hyperglycemic conditions [14].…”
Section: Resultssupporting
confidence: 93%
“…Previously, oral administration of nanocurcumin (100 mg/kg body weight per day for 30 days) appeared to suppress ROS levels in rats with diabetic cardiomyopathy [14]. However, no research on the effects of nanocurcumin on diabetic cardiomyopathy in rats has been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…For use in clinical trials, investigations into the creation of DMC‐eluting stents are now underway. Along these lines, a DMC‐carbomethyl‐hexanol chitosan nanomatrix created by our collaborator effectively inhibits VSMC migration in vitro , and a stent including this substance is now being tested to examine its effects on balloon injury induced neointima formation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that curcumin interferes with TNF‐α‐induced migration in human VSMCs by inhibiting matrix metalloproteinases (MMPs) . In addition, a DMC‐carbomethyl‐hexanol chitosan nanomatrix has been shown to effectively inhibit VSMC migration . However, it has not been shown whether DMC and BDMC can interfere with migration to the same extent as curcumin does.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the controlled release of DMC from the nanocrystallite-chitosan nanocarrier has been examined for its possibility to enhance cisplatin-induced apoptosis by downregulation of TP and ERCC1-related pathways in NSCLC. In order to accurately regulate the DMC elution, a highly biocompatible amphiphilic chitosan was employed as a drug carrier [16,17]. This amphiphilic carboxymethyl-hexanoyl chitosan (CHC) is modified from natural chitosan through carboxylmethylation and hexanoyl replacement along the backbone of pristine chitosan.…”
Section: Introductionmentioning
confidence: 99%